EFEKTIVITAS PROSES PEMBELAJARAN DARING TERHADAP MAHASISWA PENDIDIKAN OLAHRAGA DAN KESEHATAN UNIVERSITAS PASIR PENGARAIAN ANGKATAN 2020 - Sri Rahayu Br. Hombing; Ardiah Juita; Hirja Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Every research activity certainly has a purpose and objective, based on the formulation of the existing problem, the goal to be achieved in this research is to determine the effectiveness of the online learning process for sports and health education students at Pasir Pengaraian University. This research was conducted in November – April 2022. The population in this study was Students of Sports and Health Education at Pasir Pangaraian University Class of 2020. The sampling technique used a total sampling of 58 people. The data collection technique used is by giving a questionnaire. From the results of the research process to data processing which was carried out by collecting data to test the research instrument as many as 26 Riau University students stated that the 24 statements were valid, which was stated by r arithmetic > r table (0.388) and reliability test with Cronbach's Alpha value of 0.752 . after that, the researchers conducted a trial of the research instrument by distributing questionnaires (questionnaires) to 58 samples, namely students of sports and health education at Pasir Pangaraian University Class of 2020 producing data that was used as a benchmark as a discussion of research results. The Effectiveness of the Online Learning Process on Sports and Health Education Students at the Pasir Pangraian University Class of 2020 is said to be effective with a percentage of 65.74%.Key Words: Effectiveness of the Online Learning Process